Inclusive Data Visualization for People with Disabilities: A Call to Action - Marriott, Kim; Lee, Bongshin; Butler, Matthew; Cutrell, Ed; Ellis, Kirsten; Goncu, Cagatay; Hearst, Marti; McCoy, Kathleen; Szafir, Danielle Albers (Interactions, 2021)
Insights → Lack of accessible access to data visualizations is a significant equity issue. → It's not only visual impairments that can restrict access but also other kinds of disabilities including cognitive and learning disabilities, and motor disabilities. → Overcoming this challenge requires visualization practitioners, visualization and accessibility researchers, and the relevant disability communities to work together.